The dielectric parameters of a pyridine-based calamitic liquid crystal - Karanlik, Gurkan; Ocak, Hale; Canli, Nimet Yilmaz; Okutan, Mustafa; Eran, Belkiz Bilgin (IOP Publishing Ltd, 2019)
In this research, a new pyridine-based calamitic compound Methyl 5-(4-(S)-3,7-dimethyloctyloxyphenyl)pyridine-2-carboxylate (MDPC) was synthesized and the mesomorphic properties was investigated by traditional method. The dielectric parameters of MDPC showing an enantiotropic smectic A phase have also been evaluated from 44 degrees C to 100 degrees C and from 1 kHz to 2 MHz. The dielectric parameters (absorption coefficient, relaxation time and dielectric strength) have been determined by Origin Lab 8.5. This material can be used in super capacitors between 65 degrees C-95 degrees C. Furthermore, it has been found that the conductivity mechanism of the MDPC exhibits from 44 degrees C to 60 degrees C Quantum Tunneling Model (QMT) and after 60 degrees C exhibits DC conductivity mechanism and QMT mechanisms in low and high angular frequency region, respectively.
Keywords: liquid crystal; impedance spectroscopy (IS); dielectric properties (DS); Cole-Cole plot; ESTER; AZOBENZENE; MESOGENS; Materials Science